PERILAKU HIDUP SEHAT DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Abdul Rahmat; Mardia Bin Smith; Maryam Rahim (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2015)
Healthy life behavior amongst primary school students need to be reviewed concerning that healthy behavior at primary school age as a basic foundation for the healthy growth and development. Growth and healthy development would be enabling conditions for a variety of children's activities, including learning. This research aimed to grasp an overview of the correlation between health behavior and academic achievement of students. This research design was correlational with a sample size of 30 students. Based on the analysis of data, there is a significant correlation between health behavior and academic achievement of students. In this case the better the health behavior of students, the better the academic achievement.